Thermal Conductivity of Aloji Fireclay as Refractory Material - Ajala, Amkpa Job; Badarulzaman, Nur Azam (International Journal of Integrated Engineering, 2016)
This investigation was concentrated on the thermal behavior and insulating property of the Aloji fireclay for its suitability of being used as refractory lining. The Aloji fireclay brick has thermal conductivity of 0.05 K (W/m.k). Heat capacity of the brick was 0.5 J/g 0C at the minimum temperature of 93.33 0C as compared to 0.3 J/g 0C obtained at the maximum temperature of 600 0C. The heat capacity of the clay showed that as temperature increases the heat capacity changes with phase changes. The clay sample was subjected to TG+DTA analysis. The clay sample as when exposed to thermal treatment exhibited some clay material degradation with evidence of endothermic and exothermic reactions.Â